2017
DOI: 10.1073/pnas.1707680114
|View full text |Cite|
|
Sign up to set email alerts
|

Structural complexity and molecular heterogeneity of a butterfly ejaculate reflect a complex history of selection

Abstract: Male ejaculates are often structurally complex, and this complexity is likely to influence key reproductive interactions between males and females. However, despite its potential evolutionary significance, the molecular underpinnings of ejaculate structural complexity have received little empirical attention. To address this knowledge gap, we sought to understand the biochemical and functional properties of the structurally complex ejaculates of butterflies. Males in this species produce large ejaculates calle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 70 publications
1
36
1
Order By: Relevance
“…The Pieris napi genome assembly (7,829 scaffolds, N50 = 300,294) was reported to contain a conserved single‐copy ortholog content of 78% using CEGMA (Meslin et al., ). Here, this was further assessed by quantifying the content of complete BUSCO arthropod genes, which was 74% (Supporting information Table ), similar to other recently published Lepidopteran genomes, which ranged from 67.7% to 99.1% (Kanost et al., ; Supporting information Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Pieris napi genome assembly (7,829 scaffolds, N50 = 300,294) was reported to contain a conserved single‐copy ortholog content of 78% using CEGMA (Meslin et al., ). Here, this was further assessed by quantifying the content of complete BUSCO arthropod genes, which was 74% (Supporting information Table ), similar to other recently published Lepidopteran genomes, which ranged from 67.7% to 99.1% (Kanost et al., ; Supporting information Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The P. napi and P. rapae genome sequences used for the MK test were obtained from Meslin et al. (). The P. brassicae genome was constructed using a Pool‐seq library from the thoraxes of 24 Spanish butterflies (41.818225°N, 2.302625°E; 12 males and 12 females).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that by sequestering SFPs in different cells or glands males are afforded control over their release, and consequently, spatiotemporal control over their interactions with sperm, the female reproductive tract, or with other SFPs (16). Additionally, functional diversification of tissues and cell-types may be required to build specialised parts of the ejaculate, such as mating plugs (17). In either case, activities may be carried out independently between cell-types and tissues or there may be cross-talk between them that coordinates global seminal fluid composition.…”
Section: Introductionmentioning
confidence: 99%
“…Such sexual selection can also influence molecular traits and has resulted in many reproductive proteins that evolve at extraordinary rates [12,13]. For example, in the marine gastropod abalone, males produce an extraordinary number of sperm that overexpress the rapidly evolving protein lysin (up to ~1 g lysin per male abalone) that facilitates species-specific fertilization [14][15][16]; in fruit flies, males accessory glands synthesize complex mixtures of rapidly evolving seminal fluid proteins that restrict female re-mating by reducing her viability and survival [17,18]; similarly, in Pieris butterflies, males produce enormous spermatophores (~13% of their body mass) that are encased in a nearly indestructible protein shell that slows spermatophore clearance and prevents female re-mating [19]. In these examples, however, the molecular mechanisms underlying the regulated expression of these unusual reproductive proteins are not fully understood.…”
Section: Introductionmentioning
confidence: 99%